Necessity of detection of extended spectrum beta-lactamase, AmpC and metallo-beta-lactamases in Gram-negative bacteria isolated from clinical specimens - Mehvash Haider; Meher Rizvi; Nazish Fatima; Indu Shukla; Abida Malik (Wolters Kluwer Medknow Publications, 2014)
Background: With increasing incidence of resistance to antibiotics carbapenems are used as the last resort because they are stable even in response to extended spectrum and AmpC beta-lactamases. However, Gram-negative bacilli producing the acquired metallo-beta-lactamases (MBL) are on the rise. Aim: The aim of the following study is to detect phenotypically the presence of extended spectrum beta-lactamase (ESBL), AmpC and MBL in Gram-negative bacteria isolated from clinical specimen. Materials and Methods: Gram-negative isolates from clinical samples were screened and confirmed for the presence of ESBLs by double disk synergy test (DDST), for AmpC by disk approximation assay and for MBL by Modified Hodge Test and imipenem-ethylenediaminetetraacetic acid DDST. Results: Among 251 isolates studied, 138 (54.98%) were ESBL producers, 49 (19.52%) were AmpC producers and 45 (17.93%) were MBL producers. Highest rates of ESBL detection was by Cefoperazone sulbactam (109/138) 78.98%. Out of 92 of the AmpC producing strains 20 (21.73%) were inducible and 72 were stably derepressed (78.26%). Out of 251 strains studied 45 (17.93%) were phenotypically identified as MBL producers, the highest no. being of Pseudomonas aeruginosa. Among the methods employed for detection of MBL production, Hodge test (62.22%) proved better than DDST (40%). Conclusions: High level of antibiotic resistance pattern exists in various clinical isolates. ESBL production should be looked for routinely in Gram-negative bacteria other than Escherichia coli and Klebsiella. A high percentage of derepressed AmpC mutants are noteworthy and alarming. We recommend phenotypic identification methods as routine practice in laboratories as genotypic methods are not cost-effective.